Citrus flush shoot ontogeny modulates biotic potential of Diaphorina citri - Cifuentes-Arenas, Juan Camilo [UNESP]; Goes, Antonio de [UNESP]; Miranda, Marcelo Pedreira de; Charles Beattie, George Andrew; Lopes, Silvio Aparecido (Public Library Science, 2018)
The biology and behaviour of the psyllid Diaphorina citri Kuwayama (Hemiptera: Sternor-rhyncha: Liviidae), the major insect vector of bacteria associated with huanglongbing, have been extensively studied with respect to host preferences, thermal requirements, and responses to visual and chemical volatile stimuli. However, development of the psyllid in relation to the ontogeny of immature citrus flush growth has not been clearly defined or illustrated. Such information is important for determining the timing and frequency of measures used to minimize populations of the psyllid in orchards and spread of HLB. Our objective was to study how flush ontogeny influences the biotic potential of the psyllid. We divided citrus flush growth into six stages within four developmental phases: emergence (V1), development (V2 and V3), maturation (V4 and V5), and dormancy (V6). Diaphorina citri oviposition and nymph development were assessed on all flush stages in a temperature controlled room, and in a screen-house in which ambient temperatures varied. Our results show that biotic potential of Diaphorina citri is not a matter of the size or the age of the flushes (days after budbreak), but the developmental stage within its ontogeny. Females laid eggs on flush V1 to V5 only, with the time needed to commence oviposition increasing with the increasing in flush age. Stages V1, V2 and V3 were most suitable for oviposition, nymph survival and development, and adult emergence, which showed evidence of protan-dry. Flush shoots at emerging and developmental phases should be the focus of any chemical or biological control strategy to reduce the biotic potential of D. citri, to protect citrus tree from Liberibacter infection and to minimize HLB dissemination.